The Integration of Islamic and Cultural Values in English Teaching - Yatni Fatwa Mulyati; Ummi Kultsum (Institut Agama Islam Negeri Palopo, 2023)
Teaching English is closely related to learning Western culture; however, it is only sometimes about using the same material. As the country with the largest Muslim population in the world, Indonesia must play a role in integrating Islamic values into learning, mainly English as a foreign language. This study aimed to reveal the integration of Islamic and cultural values in English teaching to Islamic university students. This descriptive qualitative used semi-structured interviews and observation to gather the data. There were 42 students, and one lecturer was chosen using purposive sampling as the participants. The findings showed that integrating Islamic and cultural values helps students understand English more easily. Furthermore, it also supports students with an Islamic background. In addition, the observation result proves that students speaking, listening, translation, reading, and vocabulary achievement is outstanding during the observation. This current research strongly contributes to the literature on research about integrating Islamic values into language teaching. However, the cultural values that showed up are Islamic cultural values. Further research focusing on Local cultural integration in teaching English may be enlightening.